THE EXPRESSIONS OF REQUEST FOUND IN NANNY MC PHEE AND THE BIG BANG MOVIE BY SUSANNA WHITE: PRAGMATICS ANALYSIS - Wijayanti, Ika Ida (Universitas Muhammadiyah Surakarta, 2012)
This study is aimed at analyzing request expressions found in Nanny McPhee and the Big Bang movie by Susanna White, focusing on the pragmalinguistics for request ex- pressions, the illocution of request expression, and the request strategy in this movie. The data of this research are sentences containing request expressions found in the movie. The researcher finds 118 request expressions in the movie. The method of collecting the data in this research are watching the original Movie, note taking all the request expres- sion in the movie, and re-typing all the sentences containing request expression in the movie. The writer uses descriptive interpretive to analyze the data of request expression in the movie. The techniques of analysis are finding out request expressions in the movie, identifying the pragmalinguistics of request expressions used in the movie, clarifying the intention of request expression used by the speakers in utterances in the movie and describing request strategies used in the movie. The result of the study ara as follows:Â (1) the pragmalinguistics of the request are internal modification; Syntactic Downgrader (Question and Past Tense/ Negotion), Lexical/ Phrasal Downgrader (Politeness Marker, Hesitator), and external modification; preparators (preparing the speech act) and (2) request strategies of these findings are mood derivable, performative, obligation state- ment, want statement, suggestory, quire prepatory, and hint.